2020
DOI: 10.1519/jsc.0000000000002817
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability Between Free Weight and Machine-Based Movement Velocities

Abstract: Miller, RM, Freitas, EDS, Heishman, AD, Koziol, KJ, Galletti, BAR, Kaur, J, and Bemben, MG. Test-retest reliability between free weight and machine-based movement velocities. J Strength Cond Res XX(X): 000-000, 2018-Several devices are available to measure muscular power through velocity measurement, including the Tendo FitroDyne. The ability for such devices to produce consistent results is still questioned, and the reproducibility of measurement between free weight and machine exercise has yet to be examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
3
18
0
1
Order By: Relevance
“…Therefore, it seems that the feasibility of the individualized load-velocity relationship to predict the 1RM is more influenced by the exercise type (e.g., BP vs. deadlift) than by the execution mode (machine-guided vs. free-weight). This assumption could be further supported by Balsalobre-Fernández et al (3) who revealed a stronger (i.e., lower SEE ) load-velocity relationship for the free-weight BP exercise compared with the free-weight back squat and deadlift exercises, as well as by other studies that have revealed an acceptable and comparable reliability of velocity outputs for the same exercises performed with free weights or in a Smith machine (11,22,31). Therefore, in line with previous investigations conducted with the BP exercise performed in a Smith machine (10,25), the results of this study also suggest that the free-weight BP 1RM can be obtained with a high precision from the individualized load-velocity relationship.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, it seems that the feasibility of the individualized load-velocity relationship to predict the 1RM is more influenced by the exercise type (e.g., BP vs. deadlift) than by the execution mode (machine-guided vs. free-weight). This assumption could be further supported by Balsalobre-Fernández et al (3) who revealed a stronger (i.e., lower SEE ) load-velocity relationship for the free-weight BP exercise compared with the free-weight back squat and deadlift exercises, as well as by other studies that have revealed an acceptable and comparable reliability of velocity outputs for the same exercises performed with free weights or in a Smith machine (11,22,31). Therefore, in line with previous investigations conducted with the BP exercise performed in a Smith machine (10,25), the results of this study also suggest that the free-weight BP 1RM can be obtained with a high precision from the individualized load-velocity relationship.…”
Section: Discussionmentioning
confidence: 61%
“…The bench press (BP) is an exercise commonly used to assess upper-body pushing performance (26,30). The velocity achieved when lifting a submaximal load at maximal intended velocity is a performance indicator frequently used during BP testing procedures (2,13), which is justified by the high reliability of movement velocity observed for different variants of the BP exercise (11,22,31). However, it is unknown whether the reliability of movement velocity could be influenced by the provision of velocity performance feedback during the BP testing protocol.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the use of a Smith machine, which restricts the movement of the barbell to the vertical direction, may limit the ecological validity of our findings because athletes typically perform the back-squat exercise with free-weights. However, since it has been shown that machine-based exercises provide more reliable measures of movement velocity than free-weight exercises [ 21 ], we decided to use the Smith machine to eliminate the possible confounding factors that could be present during free-weight exercises (e.g., horizontal movements of the barbell). In addition, although it is less frequent in training, resistance training exercises are often performed in a Smith machine for testing purposes [ 11 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the back-squat exercise has been shown to report more consistent velocity measurements using the pause technique compared to the rebound technique [ 19 ]. It should be also noted that machine-based exercises can provide more reliable measures of velocity than free-weight exercises [ 21 ], and, consequently, it is common that the testing procedures of mechanical performance against submaximal loads are performed in a Smith machine to reduce the noise of the test [ 11 , 22 , 23 , 24 ]. Therefore, it seems important to compare the reliability of the different performance variables during the back-squat exercise performed in a more controlled environment (i.e., Smith machine) using both the pause and rebound techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The leg press [16,17] was performed in a Keiser leg press (Air300 Leg Press, Keiser Corporation, California, USA) and a standardized ten-repetition test was applied. Based on the participants estimated 1RM, the apparatus estimated ten loads with increasing resistance.…”
Section: Power Testing (Bench Pull and Leg Press)mentioning
confidence: 99%